Classroom lecturing regulations and mesogenetic effects: Tensions between teaching devices and situation - Weisser, Marc (Swiss Journal of Educational Research, 2012)
How does a teacher manage to regulate the exchanges between pupils in order to achieve his goals? That is the question we propose to examine within this contri- bution. We compare the course of a teaching sequence with the device previ- ously designed by the professor. The tools implemented to analyze the collected corpus are borrowed from pragmatic linguistics. The strategic places where the teacher intervenes to direct the reflection of his class are identified. The role played by its local and partial institutionalizations is specified. The conclusion presents some suggestions about the tensions between the preexistent teaching device and the situation lived into the classroom.